2007
DOI: 10.1194/jlr.m600364-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes or peroxisome proliferator-activated receptor α agonist increases mitochondrial thioesterase I activity in heart

Abstract: Peroxisome proliferator-activated receptor a (PPARa) is a transcriptional regulator of the expression of mitochondrial thioesterase I (MTE-I) and uncoupling protein 3 (UCP3), which are induced in the heart at the mRNA level in response to diabetes. Little is known about the regulation of protein expression of MTE-I and UCP3 or about MTE-I activity; thus, we investigated the effects of diabetes and treatment with a PPARa agonist on these parameters. Rats were either made diabetic with streptozotocin (55 mg/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 49 publications
5
38
1
Order By: Relevance
“…Moreover, the mechanisms underlying the induction of ACOT7 in the heart and skeletal muscle are also unclear, while the induction of ACOT1 and ACOT2 seems to be mediated by PPAR alpha. 7,25,26) We have pointed out beneficial aspects of ACOT upregulation with respect to alleviation of lipotoxicity and insulin resistance. However, it has not been determined whether the lipotoxic conditions detrimental to obese animals are associated with maladaptation of ACOT expression, because our dietinduced obesity model fed a high-fat diet, but not a Western diet, 21) showed no apparent metabolic problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the mechanisms underlying the induction of ACOT7 in the heart and skeletal muscle are also unclear, while the induction of ACOT1 and ACOT2 seems to be mediated by PPAR alpha. 7,25,26) We have pointed out beneficial aspects of ACOT upregulation with respect to alleviation of lipotoxicity and insulin resistance. However, it has not been determined whether the lipotoxic conditions detrimental to obese animals are associated with maladaptation of ACOT expression, because our dietinduced obesity model fed a high-fat diet, but not a Western diet, 21) showed no apparent metabolic problems.…”
Section: Discussionmentioning
confidence: 99%
“…20,21) Although the roles of ACOT in lipid metabolism have not been fully established, a model concerning the roles of ACOT1 and ACOT2 is emerging. 7,8,[20][21][22][23] In this model, fatty acids entering a cell across the plasma membrane are rapidly activated to acyl-CoA and partitioned into the oxidative and nonoxidative metabolic pathways. 20,21) In the heart and soleus muscle, where the expression level of cytosolic ACOT1 is very low, mitochondrial fatty acid oxidation may be the default primary pathway for acyl-CoA metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on cardiac mitochondria noted the hydrolysis of LCFA-CoA to LCFA by mitochondrial thioesterase I (MTE-I) in the matrix, and these LCFAs are subsequently exported out of the mitochondria by an unidentified protein carrier [7;8]. It has been proposed that uncoupling protein 3 (UCP3) is responsible for LCFA export from the matrix [7], however we recently observed that both MTE-I and fatty acid export are up-regulated ∼5-fold by diabetes without a significant change in UCP3 protein levels [8]. A likely candidate for this process is CD36, however it's role in mitochondrial LCFA export has not been assessed.…”
Section: Introductionmentioning
confidence: 99%